Dinamismo do comportamento resiliente: uma reflexão sobre a expatriação de brasileiros na China - Scherer, Laura Alves (2013)
This study aims to analyze the resilient behavior of Brazilian expatriates in China, in the face of expatriation experience. As a research method was adopted a qualitative, exploratory and descriptive study. Semi-structured interviews were conducted with twelve Brazilian expatriates in China, which were analyzed with the technique of content analysis (Bardin, 2011). The categories of analysis defined a priori were: the experience of expatriation, situations of adversity, dynamic of behavior resilient, and, factors and resilient results. These categories were defined based on the theoretical approach of Hofstede (1991), Grotberg (2005) and Minello (2010). Were also defined two categories of analysis not a priori - emotions and feelings related to family and perception of Chinese culture related to business - which emerged from the respondent s reports. As a result, it is emphasized that the experience of expatriation has lots of adversities in everyday situations, especially related to cultural differences between Brazilians and Chinese, like the different habits of hygiene and food smells, gestures, Chinese language, and communication in order to understand the thinking of the Chinese people. Accordingly, the first expatriates reaction was denial, manifested by anger, irritation, insecurity and disgust; This is due to the fact that such situations were not part of the mental model of Brazilians expatriates interviewed, which resulted in cultural shock. However, one of the adversities that was more evident among respondents was related to geographical distance, which generated the feeling of suffering because of missing relatives and people who were living in Brazil. In the professional environment, the timezone was an element that contributed to the stress of expatriates due to long working hours they had to do to participate in the activities of the company in both time of Brazil and China. Thus, it was possible oscillation between moments of emotional stability and moments of grief and isolation, which can be related to the dynamics of resilient behavior of expatriates, sometimes positive, sometimes negative. It is noted as resilient factors, the search for social support in co-workers, on the internet, on courses and search for groups of Brazilian or foreign, seeking to learn more about Chinese culture, Chinese and English language. For expatriates married, nuclear family (spouse and children) was more united, representing a strong emotional support to face the difficulties of expatriation together. Another result of this experience, as a consequence of the positive resilient behavior, was the opening of consciousness to understand the Chinese culture, that reflected in maturity, patience, personal development, and professional growth and development.